The Digital Entrepreneurship Ecosystem in the Central Eastern European Countries - Szerb, László; Czigler, Enikő; Horváth, Gergely Zoltán (Foresight and STI governance, 2024)
While the economic transition from a planned economy to a market economy seems to be over for most countries after 25 years, a socialist heritage could have long lasting effects. In this paper we aim to answer to the following two research questions: (1) How deeply have Central and Eastern European (CEE) countries proceeded in digital entrepreneurship? (2) Are there some specific digital entrepreneurship characteristics of the CEE countries that can be explained by their socialist heritage? We applied the Digital Entrepreneurship Ecosystem (DEE) Index methodology that relies upon a dataset for 170 countries to evaluate the former socialist CEE countries’ performance in the development of a digital entrepreneurship ecosystem. The non-EU Western countries are the best performers in Europe, but Western EU member states are close behind. The Southern European country group’s performance is close to the EU CEE country cluster, implying that these countries have caught up with most Southern European countries in their DEE development. The former SU country group and the non-EU Balkan country groups are very similar to each other. We also examined the four sub-indices and the twelve pillars and concluded that DEE scores vary significantly among European countries, but these differences can be explained by economic development and not the long-lasting effects of the socialist system. We also provided a detailed DEE profile for Russia, which explains Russia’s modest performance in the development of a digital entrepreneurship ecosystem.   Supplementary data